THE DIMENSIONS OF SCHOOL MANAGEMENT AND THEIR IMPLICATIONS FOR QUALITY OF EDUCATION - Alves, Paula Regina de Moura França; González, Daniel González (Seven Editora, 2025)
This study presents the results of a research that explored different dimensions of school management, looking for the identification of the ones that show more influence in the students learning process, based on the literature. In methodologic terms, it is a research delimited by a qualitative approach, supported by exploratory typology. To reach the goals, bibliography research was used as data collection instrument and, to analyze them, it was used a technique of content analysis. And with the research development, it was verified through the literature that the organization of school management in different dimensions influences positively the learning environment. However, the relationship between them is still linear, without hierarchizing what school management dimensions are more relevant to the academic success. As final result, this theoretic study wants to offer a conceptual basis with the purpose of enlarging knowledge and going deep on school management dimensions, showing their relevance to improve academic performance indicators and, consequently, to education improvement. DOI: https://doi.org/10.56238/sevened2025.030-083